Automatic Identification of Myeloperoxidase Natural Inhibitors in Plant Extracts - Fátima A. R. Mota; Sarah A. P. Pereira; André R. T. S. Araújo; Beatriz Gullón; Marieta L. C. Passos; Maria Lúcia M. F. S. Saraiva (Molecules, 2022)
The aim of this study is the development of an automated method for myeloperoxidase activity evaluation and its application in testing the inhibitory action of different plant extracts on the activity of the enzyme. This enzyme has its concentration increased in inflammatory and infectious processes, so it is a possible target to limit these processes. Therefore, an automatic sequential in-jection analysis (SIA) system was optimized and demonstrated that it is possible to obtain results with satisfactory accuracy and precision. With the developed method, plant extracts were studied, as promising candidates for MPO inhibition. In the group of selected plant extracts, IC50 values from 0.029 ± 0.002 mg/mL to 35.4 ± 3.5 mg/mL were obtained. Arbutus unedo L. proved to be the most inhibitory extract for MPO based on its phenolic compound content. The coupling of an automatic SIA method to MPO inhibition assays is a good alternative to other conventional methods, due to its simplicity and speed. This work also supports the pharmacological use of these species that inhibit MPO, and exhibit activity that may be related to the treatment of infection and inflammation.